The Conserved Lysine-265 Allosterically Modulates Nucleotide- and Actin-binding Site Coupling in Myosin-2 - Vincent A. Behrens; Stefan Münnich; Georg Adler-Gunzelmann; Claudia Thiel; Arnon Henn; Sharissa L. Latham; Manuel H. Taft (Scientific Reports, 2017)
Abstract Myosin motor proteins convert chemical energy into force and movement through their interactions with nucleotide and filamentous actin (F-actin). The evolutionarily conserved lysine-265 (K265) of the myosin-2 motor from Dictyostelium discoideum (Dd) is proposed to be a key residue in an allosteric communication pathway that mediates actin-nucleotide coupling. To better understand the role of K265, point mutations were introduced within the Dd myosin-2 M765-2R framework, replacing this lysine with alanine (K265A), glutamic acid (K265E) or glutamine (K265Q), and the functional and kinetic properties of the resulting myosin motors were assessed. The alanine and glutamic acid substitutions reduced actin-activated ATPase activity, slowed the in vitro sliding velocity and attenuated the inhibitory potential of the allosteric myosin inhibitor pentabromopseudilin (PBP). However, glutamine substitution did not substantially change these parameters. Structural modelling suggests that K265 interacts with D590 and Q633 to establish a pivotal allosteric branching point. Based on our results, we propose: (1) that the K265-D590 interaction functions to reduce myosins basal ATPase activity in the absence of F-actin, and (2) that the dynamic formation of the K265-Q633 salt bridge upon actin cleft closure regulates the activation of product release by actin filaments.